Capital, Gender, and Microenterprise Growth in Ghana - Fafchamps, Marcel; McKenzie, David; Quinn, Simon; Woodruff, Christopher (World Bank, Washington, DC, 2012)
Despite the emphasis placed by microfinance organizations on lending to female business owners, evidence from three recent randomized controlled trials has cast doubt on the ability of capital alone to grow female-operated microenterprises: in my own previous experiment in Sri Lanka women given grants saw no increase in business profits, while the recent randomized trials of microfinance in the Philippines and India also see very little in the way of profit increases when women get loans. One possible interpretation is that female-owned microenterprises in these countries are already operating at their efficient level of capital, which might be very low especially in countries where other labor market options for women are limited. However, an alternative explanation could be that the small scale of many female-owned firms is not efficient, but arises instead from a lack of separation of business and household accounts, and from inefficiencies in the way people allocate assets between them. These inefficiencies might arise from self-control problems, leading owners to not undertake profitable investments, or from external pressure to share with others.